2016
DOI: 10.1371/journal.pone.0159243
|View full text |Cite
|
Sign up to set email alerts
|

Frequencies of Circulating MAIT Cells Are Diminished in Chronic HCV, HIV and HCV/HIV Co-Infection and Do Not Recover during Therapy

Abstract: ObjectiveMucosal-associated invariant T (MAIT) cells comprise a subpopulation of T cells that can be activated by bacterial products and cytokines to produce IFN-γ. Since little is known on MAIT cells during HCV infection, we compared their phenotype and function in comparison to HIV and HCV/HIV co-infected patients, and determined the effect of IFN-α-based and direct-acting antiviral therapy on MAIT cells of HCV patients.MethodsBlood samples from patients with chronic HCV (CHCV), virologically suppressed HIV,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
50
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(69 citation statements)
references
References 34 publications
16
50
3
Order By: Relevance
“…1A). Consistent with previous reports 15, 20, 22 , the frequency of MAIT cells was lower in the blood of patients with chronic HCV infection than of uninfected controls (1.31%, interquartile range [IQR] 0.61%–1.92% vs 2.32%, IQR 0.96%–3.5%; P =.0048, Fig. 1B left panel).…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…1A). Consistent with previous reports 15, 20, 22 , the frequency of MAIT cells was lower in the blood of patients with chronic HCV infection than of uninfected controls (1.31%, interquartile range [IQR] 0.61%–1.92% vs 2.32%, IQR 0.96%–3.5%; P =.0048, Fig. 1B left panel).…”
Section: Resultssupporting
confidence: 91%
“…It is also consistent with the increase in the frequency of MAIT cells in the liver along with the resolution of liver inflammation by week four of antiviral therapy. In contrast, and consistent with previous reports 15, 20, 22 , antiviral therapy did not improve the reduced MAIT cell frequency in the peripheral blood even during a longer follow up to week 24 post therapy. Since the liver is equipped with a high density of immune cells, an increase in MAIT cell frequency in the blood may lag significantly behind any changes the liver.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The reduction of circulating MAIT cells was also reported in patients with chronic viral infections, including human immunodeficiency virus and hepatitis C virus, although we could not identify this reduction of MAIT cells in the blood of patients with CVH. We could not determine the reason for the discrepancy between previous studies and our study; however, the median value of ALT in the patients with CVH in our study seems to be lower than that in patients with hepatitis C virus infection in the previous studies . We speculate that our study included patients with less active liver inflammation and that MAIT cells might be less activated.…”
Section: Discussionmentioning
confidence: 99%
“…Two recent studies in HCV-infected patients have similarly found that the MAIT cell depletion and dysfunction observed in chronic HCV is not reversible even after successful interferon therapy or interferon-free therapy. 63,64 The role of MAIT cells in liver inflammation and the impact of MAIT cell perturbations on the general state of mucosal immunity in patients with these infections require further investigation.…”
Section: Mait Cells and Viral Hepatitismentioning
confidence: 99%